“Manejo del nitrógeno en el cultivo de arroz, basado en la sostenibilidad”. - Soto Moncada, Héctor Julio (2019)
SUMMARY This document was carried out in the experimental farm "San Pablo", of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km. 7.5 of the Babahoyo - Montalvo highway. The site is located between the geographic coordinates of 010 47`49 "of South Latitude and 790 32`49" of West Longitude and 8 masl. The zone presents a tropical climate, according to the classification of Holdribge is tropical humid forest, with annual temperature of 25.7 0C, a precipitation of 1845 mm / year, relative humidity of 76% and 804.7 hours of annual average heliophany . The soil is flat topography, clay loam texture and regular drainage. For the development of this practical component, a bibliographic review of different books, journals, scientific articles and web pages was compiled, which were subjected to synthesis techniques and summary on the sustainability of rice cultivation through the use of nitrogen. For information obtained, it was determined that there are empirical producers that apply without control the dosage of nutrients required by the crops, being nitrogen the fundamental constituent of chlorophyll, amino acids, essential for the rapid growth of plants and leaves and increase the number of tillers, ears for panicles and protein content in the grain; It is worth noting that worldwide, the production of food that does not cause harm is being demanded, ensuring environmental quality and health to ensure environmental sustainability and adequate food security in the people who consume it, part of what is called "green revolution" . Keywords: nitrogen, rice, sustainability